About the VI Intenational Congress of the Turkic World Mathematical Society (TWMS-2017) - Bokayev, Nurzhan (Eurasian Mathematical Journal, 2018)
About the VI Intenational Congress of the Turkic World Mathematical Society (TWMS-2017)